Making Ketchup Products to Build the Entrepreneurship Soul of the Putat Jaya Village, Sawahan District, Surabaya - S. Irbayuni; L. Susilowati (Future Science)
A large number of people in the Putat Jaya sub-district who have low income and do not have enough skills, demanding academics to participate in providing solutions. Through this community service program, it is expected to be able to provide increased capacity to conduct independent businesses, so that they can increase their income. Training and mentoring programs as a strategy to help the community. The program conducted is to provide knowledge about ways to build an entrepreneurial spirit, provide knowledge about the process of producing soy sauce products from coconut water, do product packaging and knowledge about entrepreneurial management. The results of this activity, the community is able to make soy sauce from coconut water at a very low cost but has a tasty and tasteful and good quality. Thus the community can improve their skills for entrepreneurship and increase their income.